Dermatoscopic patterns in Indian patients with discoid lupus erythematosus and correlation to the duration of disease and Cutaneous Lupus Erythematosus Disease Area and Severity Index - Saritha Mohanan; Nishant Ghodake Bapu (Wolters Kluwer Medknow Publications, 2024)
Dermatoscopic patterns of discoid lupus erythematosus (DLE) have recently been described in the literature. A temporal correlation of certain dermatoscopic features has also been proposed. There is sparse literature on dermatoscopic features seen in Indian/Asian patients with DLE and the correlation of these features with the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) score. A few of the patients of DLE coming to the dermatology outpatient department of our center in South India were evaluated by dermoscopy. Demographic details, duration of illness, location of plaques, and the CLASI scores were collected. A total of 26 plaques from 12 patients were evaluated by dermoscopy. Hair follicle effacement (n = 20) was the most common feature, followed by patchy pigmentation (n = 18), telangiectasia (n = 13), perifollicular pigmentation (n = 13), and perifollicular scaling (n = 10). There was a statistically significant difference in disease activity (CLASI) in patients with perifollicular scale and telangiectasia compared to patients without the above features. There was a significant difference in the duration of disease among patients with and without follicular red dots.